Research on the impact of the information cocoon effect on employment anxiety of university students and coping strategies - Lihao Wang; Fengda Wu (Environment and Social Psychology, 2025)
The proliferation of algorithm-based recommendation systems has transformed the way university students can access career-related information and, although it has made it more convenient, it has limited the range of available information. This filtering-down effect, called the information cocoon, has been connected with increasing employment anxiety, a hot topic in competitive labor markets. The aim of this research article was to investigate the correlation between information cocoon behavior and employment anxiety in university students and to test the mediating effect of risk perception bias and moderating effects of self-efficacy and social support. A quantitative, cross-sectional survey among 261 students of different disciplines was used. Data were analyzed using descriptive statistics, correlation, multiple regression, and mediation/moderating analyses through SPSS. Results indicated that 76.6% of participants exhibited moderate-to-high cocooning behaviors and 76.57% reported moderate-to-high employment anxiety. Information cocooning emerged as the strongest predictor of anxiety (β = .28, p < .001), with risk perception bias mediating 47.6% of the effect. Protective factors were identified, as high self-efficacy and strong social support reduced the cocoon–anxiety relationship by 53% and 43% respectively. These results point to the psychological hazards of algorithmic filtering and the possibility of specific interventions in digital literacy, career advising, and platform design to reduce employment-related anxiety.